Information sharing in oligopoly: Sharing groups and core-periphery architectures - Sergio Currarini; Francesco Feri (Games, 2021)
The trade-off between the costs and benefits of disclosing a firm's private information has been the object of a vast literature. The absence of incentives to share information on a common market demand prior to competition has been advocated to interpret information sharing as evidence of collusion. Recent contributions have looked at bilateral information sharing, showing that information sharing is consistent with pairwise stability, This paper studies the networked pattern of bilateral information sharing on market demand, focusing on the role of heterogeneous information (firms' signals have different variances). We show that while pairwise stability predicts that i.i.d. signals are always shared in groups with a symmetric internal structure (both with and without side-payment and linking costs), heterogeneous signals are shared in asymmetric core-periphery architectures, in which "core" firms have more valuable information than periphery firms.
Keywords: D43; D82; D85; L13; 330; Bayesian equilibrium; information sharing; networks; oligopoly